2013
DOI: 10.1007/s00417-013-2311-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between corneal hysteresis and optic nerve parameters measured with spectral domain optical coherence tomography

Abstract: In patients under evaluation and treatment for glaucoma, CH was more closely related to visual field MD than to structural markers of glaucoma damage as measured by SD-OCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…After adjusting for CCT, age, and axial length, corneal hysteresis was not associated with RNFL thickness measured by either polarimetry or spectral-domain optical coherence tomography. Vu et al [ 27 ▪ ] conducted a retrospective study of 131 patients with glaucoma. In a univariable model, corneal hysteresis varied as a function of mean deviation and spectral-domain optical coherence tomography RNFL thickness ( β = 0.2, P = 0.001); after multivariable analysis, however, the relationship between corneal hysteresis and RNFL did not hold.…”
Section: Corneal Hysteresis and Structural Markers Of Glaucomamentioning
confidence: 99%
“…After adjusting for CCT, age, and axial length, corneal hysteresis was not associated with RNFL thickness measured by either polarimetry or spectral-domain optical coherence tomography. Vu et al [ 27 ▪ ] conducted a retrospective study of 131 patients with glaucoma. In a univariable model, corneal hysteresis varied as a function of mean deviation and spectral-domain optical coherence tomography RNFL thickness ( β = 0.2, P = 0.001); after multivariable analysis, however, the relationship between corneal hysteresis and RNFL did not hold.…”
Section: Corneal Hysteresis and Structural Markers Of Glaucomamentioning
confidence: 99%
“…[15][16][17] We noted only modest Pearson correlations (À0.15 to À0.20) between CRF and VCDR (clinical and HRT) in our subjects. Although Vu et al 18 showed similar weak associations (r ¼ À0.11 to À0.15) of VCDR with CH, they did not report on the association with CRF. Likewise, Prata et al 19 demonstrated significant correlations with mean cup depth (r ¼ À0.34) and linear cup-disc ratio (r ¼ À0.41) in their evaluation of 42 newly diagnosed POAG patients.…”
Section: Discussionmentioning
confidence: 85%
“…Our study comprised exclusively of subjects with established glaucoma unlike the previous published studies that have included a wider range of subjects encompassing glaucoma suspects and established glaucoma. 7,14,15,18 The wider spectrum in those studies could have resulted in a higher disposition toward an association with disease severity. Therefore, it is likely that an inclusion of angle closure subjects with no evidence of optic neuropathy, such as primary angle closure suspects (PACS) and primary angle closure (PAC), may tilt our findings toward significant associations; however, the primary purpose of our study was to investigate the association of corneal biomechanical properties in PACG subjects with established optic nerve head damage.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that the modulus of cornea and sclera can be measured non-invasively and non-destructively using vibrational OCT. This will assist clinicians to better understand the influence of biomechanics on the outcome of refractive surgery [25] and some common eye diseases such as glaucoma [26]- [32], myopia [33], and keratoconus [34] [35] [36]. It has been observed that the modulus of keratoconus corneas is lower than that of normal tissue [7] and that scleral stiffening occurs in glaucoma [37] associated with increased collagen alignment and birefringence [38].…”
Section: Resultsmentioning
confidence: 99%